A Colloidal Synthesis Route Towards AgBiS2 Nanocrystals Based on Metal Xanthate Precursors. Issue 2 (14th December 2022) - Vakalopoulou, Efthymia; Knez, Daniel; Sigl, Marco; Kothleitner, Gerald; Trimmel, Gregor; Rath, Thomas
Abstract: Silver bismuth sulfide (AgBiS2 ) is showing impressive thermoelectric and photovoltaic properties and has a high potential to replace toxic cadmium or lead containing semiconductors in many applications. Herein, we report on a synthesis route for AgBiS2 nanocrystals applying metal xanthates as precursors. Silver xanthates could not be used so far in solution‐based syntheses for Ag‐containing metal sulfide nanocrystals as they are typically insoluble in organic solvents. An investigation of the synthesis process revealed that even though the silver xanthate is not soluble in the used solvent mixture consisting of octadecene and oleylamine, the decomposition of both precursors and the formation of AgBiS2 nanocrystals is initiated already at room temperature by the amine functionality of the ligand. At room temperature, primary crystallite sizes of approximately 4 nm are observed and at a reaction temperature of 200 °C, the size of the AgBiS2 nanocrystals increases to 7–8 nm. Abstract : In this study, we overcame the insolubility issue of silver xanthates in organic solvents hindering their application as precursors in colloidal nanocrystal syntheses. With the aid of the amine induced decomposition of metal xanthates, silver bismuth sulfide nanocrystals stabilized by oleylamine could be successfully prepared from metal xanthate precursors in a heat up synthesis.